Anthropometric and motor changes after one-year aerobic gymnastics training in young gymnasts - Lamošová, A.; Kyselovicová, A.; Tomková, P. (Science of Gymnastics Journal, 2021)
The purpose of this study was to investigate the effect of one-year specific aerobic gymnastics training on selected anthropometric and motor parameters in 6-11-year-old girls. 23 girls (average age in the beginning of the study was 8.04 ± 1.22 years) were involved in the study representing 2 different aerobic gymnastics sports clubs in Slovakia. The selected group completed their regular trainings and competitions for a period of one year. Measurements were taken in January 2019 and January 2020, in the middle of the preparatory period. Normality of distribution of the traits was examined using the Shapiro-Wilk test. Data were analyzed using Wilcoxon signed-rank test. Considering anthropometric parameters, there were significant changes (p=0.01) in body height, body weight and BMI. Considering motor parameters, the mean values of straddle support hold and back extension endurance test increased significantly to the level of p=0.05. The mean values of 4x10m shuttle run, standing long jump, modified push-ups, sit-ups in 60s increased significantly to the level of p=0.01. No significant changes were observed in bent arm hang test or hanging knee tucks. On the other hand, the values of 1 leg stand with eyes closed and 2-min endurance shuttle run decreased insignificantly.